2019
DOI: 10.3390/plants8090342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of SQUAMOSA-Promoter Binding Protein-Like Gene FvSPL10 from Woodland Strawberry (Fragaria vesca)

Abstract: SQUAMOSA-promoter binding protein-like (SPL) proteins are plant-specific transcript factors that play essential roles in plant growth and development. Although many SPL genes have been well characterized in model plants like Arabidopsis, rice and tomato, the functions of SPLs in strawberry are still largely elusive. In the present study, we cloned and characterized FvSPL10, the ortholog of AtSPL9, from woodland strawberry. Subcellular localization shows FvSPL10 localizes in the cell nucleus. The luciferase sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The miR156-targeted SPL10 is involved in regulating not only lateral root growth but also primary root growth [21,23]. Recently, it was reported that overexpression of FvSPL10, a SPL gene from Fragaria vesca, resulted in increased organs size, including longer root, larger oral organ and seeds [30]. We speculated that CpSPL2 and CpSPL10, two members clustered in the same group with AtSPL2/10/11 ( Fig.…”
Section: Functional Study Of the Cpspl2 And Cpspl10 Genesmentioning
confidence: 97%
See 1 more Smart Citation
“…The miR156-targeted SPL10 is involved in regulating not only lateral root growth but also primary root growth [21,23]. Recently, it was reported that overexpression of FvSPL10, a SPL gene from Fragaria vesca, resulted in increased organs size, including longer root, larger oral organ and seeds [30]. We speculated that CpSPL2 and CpSPL10, two members clustered in the same group with AtSPL2/10/11 ( Fig.…”
Section: Functional Study Of the Cpspl2 And Cpspl10 Genesmentioning
confidence: 97%
“…In rice, OsSPL14 has been found to promote panicle branching and grain productivity and OsSPL16 regulates grain yield and quality [28,29]. FvSPL10 from strawberry (Fragaria vesca) not only promotes early owering, but also increases organs size, such as longer root, larger oral organ and seeds [30]. As a class of plant-speci c gene family, some SPL genes are important candidates for improving plant agronomic traits by genetic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The ORF sequence of the ClChlM gene without the termination codon was subcloned into the 5'-terminus of the green fluorescent protein (GFP) in the pJX002-GFP vector with double enzyme digestion of XhoI and SalI (TaKaRa, Japan). The recombination plasmid pJX002-ClChlM1-GFP was transformed into A. tumefaciens strain GV3101 and then infiltrated into tobacco leaves (Xiong et al 2019). The location of the fusion protein was observed through fluorescence microscopy (Olympus BX51, Japan) 48 h after infiltration.…”
Section: Subcellular Locationmentioning
confidence: 99%
“…The FvSPL1 CDS was cloned in frame with green uorescent protein (GFP) tag in the binary vector pJX002. Subcellular localization analysis of FvSPL1 was performed as described by Xiong et al (Xiong et al 2019). GFP uorescence signal was observed by laser scanning microscopy (LSM800, Zeiss, Germany) within 2-5 days after injection, transient expression assays were repeated at least three times.…”
Section: Subcellular Localization Of Fvspl1mentioning
confidence: 99%